Performance of low-cost Concrete using Bentonite clay as a partial replacement with Cement - Usama, Muhammad; Ullah, Ubaid; Muhammad, Zaid; Abbas, Muhammad (Iraqi Journal of Civil Engineering, 2024)
Concrete is produced from millions of tons of Cement, which emits a significant amount of carbon dioxide from cement mills and contributes to global warming. Therefore, it is important to seek out less expensive and more environmentally friendly substitutes for OPC. While various substitutes are available, such as recycled glass, marble, silica fume fly ash, or agricultural waste like rice husks or wheat straw, the performance of concrete is significantly affected when bentonite is used as a replacement for Cement. This study aims to evaluate Jhelum bentonite, which is located at 32°56′ north and 73°44′ east longitude, as a replacement for Cement in different ratios (0:100, 10:90, 20:80, 30:70, and 40:60) to improve the durability of the system as more bentonite is used to replace conventional Portland cement, the workability, density, and water absorption of the new concrete all decrease. Compressive Strength, Tensile Strength, and flexural Strength of blocks and cylinders were tested after being cured for 7 and 28 days. Analysis of these strength tests revealed that the mixes containing bentonite were weaker after 7 days compared to 28 days, and the Strength of blocks was reasonable compared to cylinders.Keywords: Bentonite, Concrete, Compressive Strength, Tensile Strength.